Joe Celko's SQL for smarties : advanced sql programming - Celko, Joe (Morgan Kaufmann series in data management systems., 2011)
SQL for Smarties was hailed as the first book devoted explicitly to the advanced techniques needed to transform an experienced SQL programmer into an expert. Now, 15 years later and in its fourth edition, this classic reference still reigns supreme as the only book written by a SQL master that teaches programmers and practitioners to become SQL masters themselves! These are not just tips and techniques; also offered are the best solutions to old and new challenges. Joe Celko conveys the way you need to think in order to get the most out of SQL programming efforts for both correctness and performance. New to the fourth edition, Joe features new examples to reflect the ANSI/ISO Standards so anyone can use it. He also updates data element names to meet new ISO-11179 rules and he expands coverage of SSD, parallel processors and how new hardware will change how SQL works, all with the same experience-based teaching style that made the previous editions the classics they are today. KEY FEATURES Expert advice from a noted SQL authority and award-winning columnist who has given ten years service to the ANSI SQL standards committee Teaches scores of advanced techniques that can be used with any product, in any SQL environment, whether it is an SQL 92 or SQL 2008 environment Offers tips for working around deficiencies and gives insight into real-world challenges.